The moderating role of perceived organisational support on the effect of the leader member exchange relationship and power distance on occupational stress among employees in a military training unit - Nxumalo, Gugu Ntobeko (Stellenbosch : Stellenbosch University, 2024)
Thesis (MCom)--Stellenbosch University, 2024.